IMPLEMENTATION OF VILLAGE GOVERNANCE BASED ON PRINCIPLES OF GOOD GOVERNANCE OF PUBLIC SERVICE IN INDONESIA - Junaedi, Junaedi (International Journal of Business, Law, and Education, 2023)
Implementation of Village Government Governance in Indonesia according to the Principles of Good Governance. Government in the village is carried out by village officials, and the leader of a village is referred to as the village chief. Good and responsible government cannot be realized without the community's participation in and support for the implementation of the desired government. If properly utilized, the community's vast potential and resources will significantly contribute to the development of the community and the village. Numerous experiences demonstrate that governance and development without public participation will be fraught with difficulties. In light of this, government actors must recognize that the community should be engaged in every phase of government and development programs. Communities are irreplaceable stakeholders due to their strategic roles and potential for the continuity of village administration and development.